Loss of full-length pumilio 1 abrogates miRNA-221-induced gene p27 silencing-mediated cell proliferation in the heart - Yue Zhou; Denise YuEn Ng; Arthur Mark Richards; Peipei Wang (Elsevier, 2022)
Upregulated expression of microRNA (miR)-221 is associated with downregulation of p27 and subsequent increased cell proliferation in a variety of human cancers. It is unknown whether miR-221 mimics could trigger neoplastic cellular proliferation. In vitro, we demonstrated miR-221 significantly downregulates the expression of P27 and increases proliferation of H9c2 and cardiac fibroblasts. The knockdown of PUM1 but not PUM2 abolished such effects by miR-221, as verified by RT-qPCR and western blot, direct binding of p27 3' UTR by luciferase reporter assay and cell proliferation by Ki67. In vivo expression of P27 in the rat liver, heart, kidney, spleen, and muscle were not affected by miR-221 at 1 and 4 mg/kg and concurrently full-length (FL) PUM1 (140 kDa) was not detected. Instead, isoforms of 105 and 90 kDa were observed and generated through alternative RNA slicing verified by cDNA cloning and sequencing and cathepsin K cleavage confirmed by studies with the inhibitor odanacatib. This is the first study to address the possible pro-proliferative effects of miR-221 mimic therapeutics in cardiovascular applications. Loss of FL PUM1 expression is a key factor abrogating miR-221-mediated p27 regulation, although other concurrent mechanisms cannot be excluded. Our findings provide essential insights into the context-dependent nature of miRNA functionality.